Parental smoking and cessation during pregnancy and the risk of childhood asthma - Maijakaisa Harju; Leea Keski-Nisula; Leena Georgiadis; Seppo Heinonen (BMC, 2016)
Abstract Background To evaluate the association between maternal and paternal smoking during pregnancy, and asthma among offspring. Methods We conducted a hospital-based birth retrospective observational birth cohort study in a University-based Obstetrics and Gynecology Department, Kuopio University Hospital, Finland. 39 306 women, delivering between 1989 and 2006, were linked to the national register for asthma reimbursement for their offspring (2641 asthmatics). Pregnancy factors were recorded during pregnancy. Results The risk of asthma was significantly elevated if both parents smoked (aOR 3.7; 95 % Cl 3.2-4.4) and it remained high in only paternal smoking families (aOR 2.9; 95 % Cl 2.5-3.3) as well as only maternal smoking families (aOR 1.7; 95 % Cl 1.2-2.2). Paternal cessation of smoking during pregnancy seemed to reduce the risk of asthma regardless of maternal smoking (aOR 0.3-0.4). Conclusions Parental smoking, and especially paternal smoking, was significantly associated with the risk of asthma in offspring and paternal cessation of smoking during pregnancy was associated with a decreased risk of childhood asthma regardless of maternal smoking. The results indicate that both parents should be encouraged to quit smoking during pregnancy, since it is a relatively easy and cheap way to reduce the risk of asthma in offspring. Trial registration The study is registered in Kuopio University Hospital register (TUTKI): ID5302448